Real Exchange Rate Response to Capital Flows in Mexico : An Empirical Analysis - Dabos, Marcelo (IMF Working Papers; Working Paper, 2000)
This study shows that in Mexico there is a long-run relationship between the real exchange rate and capital inflows, the external terms of trade, and productivity in the manufacturing sector. A once-and-for-all unit increase in the ratio of quarterly capital inflow to quarterly (annualized) GDP causes a long-run real appreciation of the peso of about 12 percent. The analysis also reveals a structural break in 1995, which coincides with the change to a floating exchange rate arrangement, and an overvaluation of the peso in real terms on the eve of the end-1994 crisis in the range of 12 to 25 percent.